Cockatoo, Too - Murguia, Bethanie Deeney (New York, New York : Little Bee Books, 2016)
"Two cockatoos meet two more cockatoos in tutus and two tutued toucans. And then two more! Can they all can-can? They can! The cockatoos and toucans join together for a dance and ask the reader: 'Can you can-can, too?'"--Provided by publisher.
Keywords: Cockatoos -- Juvenile fiction; Toucans -- Juvenile fiction; Dance -- Juvenile fiction; Cockatoos -- Fiction; Toucans -- Fiction; Dance -- Fiction; Humorous Stories